(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Abdominal pregnancies, a rare form of ectopic pregnancy, pose significant risks to the mother and fetus. The severity of complications depends on the gestational age at presentation, abdominal pregnancy location, and attachment to abdominal organs. Case presentation: A 38-year-old, para 3+0 gravida 4 presented with abdominal pain and moderate pallor at 30 weeks gestational age, extrapolated from obstetric ultrasound due to an unknown last normal menstrual period. She was HIV-positive and on highly active antiretroviral therapy. She had a history of oral contraceptive use before conception. Ultrasound revealed a viable intraabdominal pregnancy at 30 weeks with the placenta attached to the mesentery in the right upper quadrant with a nongravid uterus. She was transfused with four units of packed red blood cells before elective laparotomy. Intraoperatively, the gestational sac in the upper quadrants and membranes were ruptured. A live male infant was delivered, weighing 990g, Apgar scores of 8 at 1 and 9 at 5. The placenta, which was attached to the left fallopian tube and the broad ligament was extracted. The infant was admitted to the newborn unit because of prematurity. The postoperative period was uneventful, and the mother and baby were doing well at the writing of this abstract. Conclusion: Early preterm abdominal pregnancy should be managed by elective laparotomy to optimize outcomes for both the mother and fetus. Cases with limited attachment to the viscera tend to have favorable outcomes. Neonatal outcome primarily depends on gestational age at delivery.